Technical supervision in criminal proceedings - Buzescu, Gheorghe (Technium Social Sciences Journal, 2024)
The principle of finding out the truth is one of the fundamental principles of the criminal process. Within it, the reactions of the individual who harm the values protected by criminal norms are analyzed, aiming to guarantee the rights of the parties and other participants, as well as the efficient exercise of the duties of the judicial bodies. Although the purpose of criminal proceedings is no longer effectively enshrined in the Code of Criminal Procedure, the notion is nevertheless found in Article 8 of the Code of Criminal Procedure under the title "Fairness and reasonable term of criminal proceedings". It stipulates that criminal prosecution and trial must be conducted in compliance with procedural guarantees and the rights of parties and procedural subjects in such a way that facts constituting criminal offences are ascertained in a timely and complete manner, no innocent person is held criminally responsible and any individual who has committed a crime is punished according to law, within a reasonable time. According to Article 97 para. (1) Code of Criminal Procedure, evidence is those realities, events, circumstances that serve to establish the existence or non-existence of a crime, as well as to the identity of the person who committed it. Thus, evidence comprises three interconnected and interdependent elements: evidence, means of proof and evidentiary procedures. The literature states that by introducing this system, "a more effective control over the manner of taking evidence can be established. Moreover, the analysis of the evidence will be possible only in terms of form, so that it complies with the law, while the analysis of the evidentiary procedures will concern the technical operation by which that means of evidence was obtained." The use of technical supervision as an evidentiary procedure in criminal proceedings is a topical topic, given the technological leap in communication and information that has taken place in recent years. We note that in the title dedicated to evidence (Title IV) of the New Code of Criminal Procedure we find a new chapter (Chapter IV), which refers to special surveillance or investigation techniques. This legislation seeks to strike a balance between ensuring the State's right to use new evidentiary procedures and respecting the right to privacy and the secrecy of correspondence. Thus, Article 138 para. (1) The Code of Criminal Procedure expressly and exhaustively provides for special technical surveillance techniques, as follows: letter (a) interception of conversations and communications; lit.(b) access to an information system; lit.(c) video, audio or photographic surveillance; (d) tracking or tracing by technical means; lit.(e) obtaining data on a person's financial transactions. Interception is defined as the intervention of authorized bodies in any kind of conversations or in any other electronic means of communication involving the idea of confidentiality. The results of the technical surveillance activity are recorded in the report, which will thus become a genuine means of evidence, being concluded in accordance with the provisions of Article 143 of the Criminal Procedure Code. Also, Articles 139-146 of the Code of Criminal Procedure provide for the cases that allow such restrictive measures against human rights and freedoms to be taken, the conditions to be met, the bodies authorized to carry out these activities, as well as the ways of verifying these means of evidence. Obtaining evidence by means of these special evidentiary procedures requires a carefully organized activity consisting in tracking the data subjects, the activities they carry out, the individuals with whom they come into contact, as well as the interception of any communication dip between them. This type of evidence was appreciated as a real modernization of the evidentiary system in criminal proceedings